Heterogeneous immigrants and foreign direct investment: The role of language skills - Matthias Lücke; Tobias Stöhr (Kiel Institute for the World Economy (IfW), 2015)
We investigate the interplay of language skills and immigrant stocks in determining bilateral FDI out-stocks of OECD reporting countries. Applying a Poisson panel estimator to 2004-2011 data, we find a robust positive effect of bilateral immigrants on bilateral FDI - provided that residents of the two countries have few language skills in common. We find a similar effect for immigrants from third countries that speak the language(s) of the FDI host country, making them potential substitutes for bilateral migrants. Our findings suggest that immigrants facilitate outgoing FDI through their language skills, rather than through other characteristics like cultural familiarity.
Keywords: F21; F22; O14; 330; migration; FDI; foreign languages; globalization